The design & development of a mascot character for SUKMA xiii Melaka 2010 / Azahar Harun … [et al.] - Harun, Azahar; Samuri, Baharim; Ali, Ariff; Abd Razak, Mohamed Razeef; Tengku Hariffadzillah, Tengku Shahril Norzaimi (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
As the host for SUKMA XIII Games, the State Government of Melaka has decided to use a legendary animal Sang Kancil as the official mascot to represent the state in 2010.Hence the Faculty of Art & Design was given the honor to develop a new mascot design for the purpose of promotion and merchandising program. In this project, we demonstrate the process of developing a new mascot concept. A standard design procedure was used as a method for the development. This procedure includes SWOT Analysis, idea brainstorming, sketches, colour scheme process, personification, prototyping and final design. In order to make an impact, emphasis is given on certain parts like eye, body posture, facial expression and costume. A triangular form is used as the base of design to enhance visual stability and dynamism. The final output consists 1 main mascot and 32 action mascots.